Hybrid Recanalization for the Treatment of Carotid/Vertebral In-stent Restenosis or Occlusion: Pilot Surgery Experiences From One Single Center - Wang, Chao; Zhao, Peng; Sun, Tao; Han, Mengtao; Wang, Yunyan; Wu, Wei; Li, Xingang; Wang, Donghai (Frontiers in Neurology, 2020)
Background: The hybrid recanalization of internal carotid artery (ICA) and vertebral artery (VA) in-stent restenosis or occlusion using a combination of endarterectomy and distal endovascular angioplasty has achieved technical success. We present our surgical experiences to further evaluate the safety and efficacy of the hybrid technique for the treatment of in-stent restenosis and occlusion. Methods: A cohort of 12 refractory patients with in-stent restenosis or occlusion who underwent hybrid recanalization, a combination of endarterectomy and distal endovascular angioplasty, were retrospectively analyzed. Medical records including presenting symptoms, comorbidities, contralateral ICA/VA findings, use of antiplatelet drugs, postoperative complications, and angiographic outcomes were collected. Results: Among 415 consecutive patients with ICA, common carotid artery, and V1 segment lesions, 12 refractory patients (2.89%) with 13 cases were enrolled in our study (1 female and 11 male). All patients underwent successful hybrid recanalization. There were no cases of postoperative stroke or death. Only 2 patients sustained hoarseness, but it resolved within 2 weeks after surgery. 3 patients were treated with dual antiplatelet (aspirin and clopidogrel), 7 with single antiplatelet (aspirin), 1 with single antiplatelet (clopidogrel), and 1 with single antiplatelet (ticagrelor). All patients were followed-up in the outpatient department according to the protocol, with a mean follow-up period of 13 months (range, 6-24 months). No death or recurrent stroke occurred during the regular follow-up period. Conclusion: The hybrid technique is a safe and feasible treatment option to recanalize in-stent restenosis or occlusion with acceptable complications.